Dependence of transcriptional repression on CpG methylation density. - Hsieh, C L (1994)
CpG methylation is known to suppress transcription. This repression is generally thought to be related to alterations of chromatin structure that are specified by the methylation. The nature of these chromatin alterations is unknown. Moreover, it has not been clear if the methylation repression occurs in an all-or-none fashion at some critical methylation density, or if intermediate densities of methylation can give intermediate levels of repression. Here I report a stable episomal system which recapitulates many dynamic features of methylation observed in the genome. I have determined the extent of transcriptional repression as a function of four densities of CpG methylation. I find that the repression is a graded but exponential function of the CpG methylation density such that low levels of methylation yield a 67 to 90% inhibition of gene expression. Higher levels of methylation extinguished gene expression completely. Transcription from methylated minichromosomes can be increased by butyrate treatment, suggesting that histone acetylation can reverse some of the repression specified by the methylated state. Sites of preferential demethylation occurred and may have resulted from transcription factor binding or DNA looping.